Characterization of hybrid chondroitin/dermatan sulfate octasaccharide domains in human brain by ion mobility tandem mass spectrometry - Ica Raluca (Proceedings of the International Symposium on Analytical and Environmental Problems, 2022)
We report here on the introduction of a rapid, highly sensitive and reliable approach in a single run, based on ion mobility separation (IMS), high resolution and tandem MS (MS/MS) by collision-induced dissociation (CID) for compositional and structural elucidation of neural chondroitin sulfate (CS) and dermatan sulfate (DS) domains, which implies the determination of the epimerization and the sulfation code of regular and irregular structures. By IMS MS and CID MS/MS, we were able to characterize in details CS/DS octasaccharides from brain obtained after CS/DS chain depolymerization by chondroitin B lyase and to detect sequences that were never found before in the octasaccharide domains of the investigated CS/DS brain fraction.